Efektifitas Pelatihan Keterampilan Tenaga Kerja Dalam Meningkatkatkan Produktivitas: (Kajian Pada Mebel Batang Kelapa di Kelurahan Kota Uneng Kabupaten Sikka) - Yosef Moan Banda (Program Studi Pendidikan Ekonomi, Universitas Flores, 2019)
The focus of this study is the skills training activities for the workforce and the inhibiting factors that affect the level of productivity of coconut stem furniture. There are three problems to be examined in this study are (1) Are there training activities for workere (2) The extent of the influence of labor on the productivity of coconut bar furniture (3) Are there any inhibiting factors in producing coconut stem furniture. This type of research is qualitative and quantitative integrated. With research subjects as many as 10 respondents consisting of 10 workers and managers. The instrument used for data collection in the form of observation, interviews, questionnaires and documentation, the data collected is then processed and analyzed using the product moment correlation coefficient formula. The results showed that there was a significant influence of the training of the skills of the workforce possessed in increasing the productivity of Maumere coconut stem furniture.